The Drosophila mutant tetanic interacts with a gene complex including the structural locus of K[+] channels and shows altered dephosphorylation and learning. - Orgad, S.; Llamazares, S.; Dudai, Y.; Ferrus, A. (European Journal of Neuroscience, 1989)
The tetanic (tta; X.-52.6) mutation has been isolated on the basis of its sensitivity to extradoses of the normal Shaker gene complex (ShC) where the K+ channel la is encoded. The mutant shows up to threefold elevation of the membrane bound protein phosphatase type 1 (PP1) activity in body extracts, probably due to reduced levels of the PP1 specific inhibitor 2 (I-2). By contrast, PP1 activity in the head is only half of the normal value. In addition, tta fails to perform normally in a negative reinforcement olfactory paradigm. The functional relationships between phosphorylation, K+ currents, phosphatase activity and modulation of synaptic activity during learning and memory are discussed in the light of their possible genetic links.